PENGEMBANGAN E-MODUL DENGAN PENDEKATAN STEM BERBASIS VIDEO ANIMASI UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MATEMATIKA SISWA KELAS VIII-3 SMP NEGERI 1 PADANGSIDIMPUAN - Halimatussakdiyah Harahap; Roslian Lubis; Marzuki Ahmad (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2026)
This research aims to develop a video animation-based E-module with a STEM approach, which is expected to enhance students' critical thinking skills in mathematics learning, particularly in the material of linear equations in one variable. Critical thinking skills are essential for 21st-century students as they can improve analytical, evaluative, and problem-solving abilities. The research method used is Research and Development (R&D) with the 4D model, which includes the stages of Define, Design, Develop, and Disseminate. The subjects of the study are 34 students from class VIII-3 at SMP Negeri 1 Padangsidimpuan. The data collection instruments consist of validation sheets from material experts, media experts, and language experts, student response questionnaires, and tests of mathematical critical thinking skills before and after the use of the E-module. The results show that the developed E-module received a validity score of 95.66% (very valid), practicality of 87.12% (very practical), and effectiveness of 93.84% (very effective). Based on these results, the video animation-based E-module with a STEM approach is deemed suitable as an innovative, interactive, and contextual alternative learning media to enhance students' critical thinking skills.